Development and Initial Validation of Military Deployment-Related TBI Quality-of-Life Item Banks. Issue 1 (January 2016) - Toyinbo, Peter A.; Vanderploeg, Rodney D.; Donnell, Alison J.; Mutolo, Sandra A.; Cook, Karon F.; Kisala, Pamela A.; Tulsky, David S.
Abstract : Objective: To investigate unique factors that affect health-related quality of life (QOL) in individuals with military deployment–related traumatic brain injury (MDR-TBI) and to develop appropriate assessment tools, consistent with the TBI-QOL/PROMIS/Neuro-QOL systems. Participants: Three focus groups from each of the 4 Veterans Administration (VA) Polytrauma Rehabilitation Centers, consisting of 20 veterans with mild to severe MDR-TBI, and 36 VA providers were involved in early stage of new item banks development. The item banks were field tested in a sample ( N = 485) of veterans enrolled in VA and diagnosed with an MDR-TBI. Design: Focus groups and survey. Outcome Measures: Developed item banks and short forms for Guilt, Posttraumatic Stress Disorder/Trauma, and Military-Related Loss. Results: Three new item banks representing unique domains of MDR-TBI health outcomes were created: 15 new Posttraumatic Stress Disorder items plus 16 SCI-QOL legacy Trauma items, 37 new Military-Related Loss items plus 18 TBI-QOL legacy Grief/Loss items, and 33 new Guilt items. Exploratory and confirmatory factor analyses plus bifactor analysis of the items supported sufficient unidimensionality of the new item pools. Convergent and discriminant analyses results, as well as known group comparisons, provided initial support for the validity and clinical utility of the new item response theory–calibrated item banks and their short forms. Conclusion: This work provides a unique opportunity to identify issues specific to individuals with MDR-TBI and ensure that they are captured in QOL assessment, thus extending the existing TBI-QOL measurement system. Abstract : Supplemental Digital Content is Available in the Text.